2022
DOI: 10.3390/lubricants10080193
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Graphene Nanosheets on Thermo-Physical and Tribological Properties of Sustainable Cutting Fluids for MQL Application in Machining Processes

Abstract: The growing need to increase productivity and pressures for more sustainable manufacturing processes lead to a shift to less harmful lubrication systems that are less harmful to nature and the people involved. The minimal quantity lubrication system (MQL) stands out in this respect, especially in interrupted cutting processes such as milling, due to the cutting interface’s highly dynamic and chaotic nature. Using graphene sheets in cutting fluids also increases the efficiency of machining processes. This work … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 54 publications
0
2
0
Order By: Relevance
“…In the last decade, exponential growth in scientific research on NPECs has been observed. However, the properties of NPECs vary depending on their production, particle size, dispersion, and concentration [101]. The presence of nanoenhanced phases modifies the thermal conductivity, viscosity, and wettability of the base fluid and can produce a lubricating film at the processing interface [102].…”
Section: Thermophysical Propertiesmentioning
confidence: 99%
“…In the last decade, exponential growth in scientific research on NPECs has been observed. However, the properties of NPECs vary depending on their production, particle size, dispersion, and concentration [101]. The presence of nanoenhanced phases modifies the thermal conductivity, viscosity, and wettability of the base fluid and can produce a lubricating film at the processing interface [102].…”
Section: Thermophysical Propertiesmentioning
confidence: 99%
“…The behavior of different nanofluids has been recently studied [20][21][22][23][24][25]. However, nanoparticles at interfaces are of particular interest.…”
Section: Introductionmentioning
confidence: 99%